INTENSIVE METHODS OF TEACHING SPECIALISTS TO ENGINEERING STUDENTS - Kahharov Abdurakhim Abdubannaevich; Ogalikov Mirzaakbar Botiralievich (Journals Park Publishing, 2023)
The article contains recommendations on the effectiveness of teaching the subject "Internal combustion engines" using digital software pedagogical tools in technical technical schools.
Keywords: professional competence, technique, teaching methods, tool, IOD, virtual experience stand.